Complex entanglements: the intersubjective as grounds for political and moral subjectivities in Through the darkness and Mukiwa: a white boy in Africa - Ngoshi, Hazel T. (Unisa Press, 2016)
Zimbabwe's complex national political economy is fertile ground for the formation of problematic political and moral subjectivities, especially in self narratives. This article analyses two Zimbabwean autobiographical narratives by considering the interplay of political power structures, personal experiences, race and how narrating subjects are conscious of all this . Questions of autobiographical subjectivities are never far from being entangled in the political, the moral and personal experiences. Above all subject's relations with others also from the grounds for subjectivity. By appropriating Sarah Nuttaill's (2009) ideas of entanglement, the article will thus consider how the narrators' subjectivities are realised intersubjectively through an analysis of the relations between the narrating subjects, their experiential histories and others. Since individual identities are understood politically, discursively and morally, the article also grapples with the question of political, cultural and moral agency, which is in turn implicated in the constitution of autobiographical subjectivity. The article concludes that the narrating subjects' identities are embedded in the entanglements with history, race and complicity with political power practices.